Pembinaan Kepemimpinan dalam Meningkatkan Komunikasi Organisasi pada Anggota OSIS SMAK Immanuel - Dompak, Timbul; Purwanti, Angel; Abidin, Sholihul; Wong, Angeline; Gea, Ras Gustini; Simatupang, Indri Anggi (PUAN INDONESIA, 2025)
Leadership is influencing other people to support the achievement of relevant organizational goals. Leadership is an art of ability or technique to make a group of people follow or comply with whatever is desired and make them enthusiastic about following it. Leadership is the art of influencing other people, such as the use of influence, action, or behavior, a form of persuasion, leadership as a means of achieving goals, the result of interaction, and so on. As a leader, you should also be able to speak in public and make presentations. Converting an oral message to an audience is essential in conveying ideas and messages to be widely understood. For this reason, SMAK Immanuel Batam students must be prepared as early as possible to speak well in public. This program was implemented at SMAK Immanuel Batam, where OSIS members were for class X Science and Social Sciences. This exercise uses training as a means of carrying out community service. Mentoring or lectures, conversations, and practice are part of the training, including public speaking techniques and developing presentation concepts. These exercises help participants learn how to manage nervousness and fear when giving a public speech and how to develop a practical presentation of ideas. The students enjoyed the activities, which lasted for 5 days.